2015
DOI: 10.1080/1745039x.2014.995972
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing the dietary tryptophan to lysine ratio on plasma levels of tryptophan, kynurenine and urea and on production traits in weaner pigs experimentally infected with an enterotoxigenic strain ofEscherichia coli

Abstract: This experiment examined if immune system stimulation of weaner pigs, initiated by inoculation an enterotoxigenic strain of Escherichia coli (ETEC), increased the requirement for dietary tryptophan (Trp), modulated the inflammatory response, altered plasma levels of Trp and its metabolite kynurenine (Kyn) and effected post-weaning diarrhoea. Individually housed pigs (n = 72) weaned at 21 d of age were allocated to one of six treatments (n = 12) according to a two by three factorial arrangement of (1) with or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…3), respectively. These results are in agreement with previous studies, (Shen et al 2012;Capozzalo et al 2015;Norgaard et al 2015) which reported that increasing the dietary SID Trp : Lys, resulted in a linear decline in PUN content in weaned pigs. Therefore, these levels might not be sufficient for piglets reared under commercial production conditions, whereby the chances of infections are high, and especially during the immediate post-weaning period.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…3), respectively. These results are in agreement with previous studies, (Shen et al 2012;Capozzalo et al 2015;Norgaard et al 2015) which reported that increasing the dietary SID Trp : Lys, resulted in a linear decline in PUN content in weaned pigs. Therefore, these levels might not be sufficient for piglets reared under commercial production conditions, whereby the chances of infections are high, and especially during the immediate post-weaning period.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, under CL conditions, the PUN concentration on day 14 declined as the dietary Trp : Lys increased. These results are in agreement with previous studies, (Shen et al 2012;Capozzalo et al 2015;Norgaard et al 2015) which reported that increasing the dietary SID Trp : Lys, resulted in a linear decline in PUN content in weaned pigs. A decrease in PUN indicates either an increase in nitrogen use efficiency or a decrease in protein breakdown, which could be a result of anabolic factors such as growth hormone or protein synthesis (Shen et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Both authors hypothesised that IS litters were experiencing weaning as a less stressful event because there were already habituated with separation from the sow. The current study attempted to study this theory further by measuring behaviour and injury scores as well as plasma cortisol and Hp, two blood markers that are often increased at the time of weaning [ 25 29 ] (to be discussed in more detail below).…”
Section: Discussionmentioning
confidence: 99%
“…and posFecal score; fecal coliforms count6 dpi[101]48d28NoF4 + O1492 × 10 10 CFU/mLFrom 1 to 2 dpwNADiarrhea, ETEC shedding in feces11 dpi[100]524d28NoF4+ O1496, 8 and 10 mL of 3.44 × 10 8 CFU/mLFrom 5 to 7 dpwNADiarrhea; ETEC fecal shedding7 dpi[112]68d28NoF43 mL of 3 × 10 10 CFU/mL7 dpwNeg. groupDiarrhea; ETEC shedding in feces; Post-mortem examination7 dpi[104]76d 25NoF4% mL of 5 × 10 8 CFU/mLAt weaningNADiarrhea; ETEC shedding in feces7 dpi[99]824d 21NoF46, 8 and 10 mL of 2.16 × 10 8 CFU/mLFrom 3 to 6 dpwNegDiarrhea: haemolytic E. coli fecal shedding11 dpi[103]912d21YesF4ac2 mL of 5.0 × 10 9 CFU/mLFrom 3 to 4 dpwNegGeneral condition scores of pigs behaviour; diarrhea; RT g ; fecal fae and est-II concentrations7 dpi[45]107d28NoF41.5 mL of 10 × 10 10 CFU/mL14 dpwNADiarrhea; E. coli in feces; blood Igs28 dpi[107]1110d24NoF41.5 mL of 10 × 10 8 CFU/mL7 dpwPosDiarrhea; ETEC shedding in feces; blood total IgA and F4ac-specific IgA14 dpi[13]125d21NoF41 mL of 1 × 10 9 CFU/mL7 dpwNeg and PosDiarrhea8 dpi[105]136d21NoF41 mL of 1 × 10 9 CFU/mL9 dpw…”
Section: Setting Of the Challenge Modelmentioning
confidence: 99%
“…However, it should be considered that the passive immunity derived from sow milk immunoglobulins can influence the piglet’s response to the pathogen, causing reduced infection effectiveness. Therefore, the majority of studies have carried out the first ETEC challenge at from 3 or 4 d post-weaning [45, 46, 67, 86, 103] to 1-week post-weaning [12, 44, 104106] due to the consideration that, during this time period, passive immunity decreased, and the piglets were still affected by the critical issues resulting from weaning. However, the effectiveness of the ETEC challenge probably depends on the weaning age and on the weight of the piglet.…”
Section: Setting Of the Challenge Modelmentioning
confidence: 99%